Lymph node removal enhances corneal graft survival in mice at high risk of rejection - Plšková, Jarmila (BioMed Central, 2004)
BACKGROUND: As shown previously, the submandibular (SM) lymph node (LN) is required for priming the immune response during corneal graft rejection. In this study, we wished to determine whether corneal grafts at "high-risk" of rejection were also protected after selective SM LN removal and if so to investigate whether this improved corneal graft survival was due to induction of specific regulatory/suppressor cells or was due to immunological "ignorance". METHODS: Two sets of experiments were performed. (1) Adoptive transfer of possible regulatory splenocytes from mice with long-term accepted corneal graft after SM LN removal. (2) SM LN removal and corneal grafts in "high-risk" hosts, which had been (A) subjected to corneal trauma with vascularization or (B) allosensitized by previous corneal graft or (C) allosensitized by previous skin graft. RESULTS: Adoptive transfer of splenocytes from tolerant mice after SM LN removal did not enhance corneal graft survival in naive recipients (p > 0.05). SM LN removal in mice with corneal vascularization enhanced corneal allograft survival compared to grafted controls with/without vascularization (p < 0.0001). The removal of the SM LN in mice, who had already been allosensitized by a previous corneal graft, did not statistically prolong corneal graft survival (p > 0.05). SM LN removal procedure did not delay rejection of corneal grafts in mice allosensitized by a previous skin transplant with the same strain combination (p > 0.05). CONCLUSION: The results suggest that removal of the SM LN in "high-risk" mice prevents rejection by mechanisms involving immune "ignorance", since prior allosensitization prevents graft acceptance after LN removal. In allosensitized recipients the stronger the allosensitization (skin- vs. corneal graft-presensitization) the greater the possibility of priming for rejection at alternative draining LN sites.